2018
DOI: 10.1161/atvbaha.118.311118
|View full text |Cite
|
Sign up to set email alerts
|

VEGF (Vascular Endothelial Growth Factor) Induces NRP1 (Neuropilin-1) Cleavage via ADAMs (a Disintegrin and Metalloproteinase) 9 and 10 to Generate Novel Carboxy-Terminal NRP1 Fragments That Regulate Angiogenic Signaling

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…NRP‐1 is a membrane protein that acts as a receptor for VEGF165 VEGF189 and is expressed in many types of tumors and regulates tumor cell proliferation, migration, and invasion . It is reported that the binding of VEGF and NRP‐1 has a specific effect on endothelial cell signal transduction and plays an important role in endothelial cell migration and angiogenesis . As a coreceptor of VEGF, NRP‐1 has great clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…NRP‐1 is a membrane protein that acts as a receptor for VEGF165 VEGF189 and is expressed in many types of tumors and regulates tumor cell proliferation, migration, and invasion . It is reported that the binding of VEGF and NRP‐1 has a specific effect on endothelial cell signal transduction and plays an important role in endothelial cell migration and angiogenesis . As a coreceptor of VEGF, NRP‐1 has great clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of CD105 has been shown to disrupt angiogenesis in tumor tissue, and CD105 -BM-MSCs are more prone to differentiate into adipocytes and osteocytes 11,46 . ADAMTS9 is expressed during ossification and also may regulate angiogenic signaling induced by VEGF 47,48 . Our results together with the previous evidence suggested that the co-regulation of osteogenesis and angiogenesis by osteoblast precursor is a complex network involving multiple genes whose regulation effect sometimes are in opposite directions.…”
Section: Osteoblast Precursor Induce Angiogenesis During Coupling Witmentioning
confidence: 99%
“…vascular [37,38]. Elevated neuropilin-1 in urinary and renal tissues is associated with the clinical response of renal lupus nephritis [35].…”
Section: Plos Onementioning
confidence: 99%